Statistics of the field‐aligned currents at the high‐latitude energetic electron boundaries in the nightside: Cluster observation. Issue 3 (3rd March 2016) - Ren, Jie; Zong, Q. G.; Zhou, X. Z.; Zhang, Hui; Fu, S. Y.; Wang, Y. F.; Liu, Yong C.‐M.
Abstract: Magnetic field disturbances with a clear bipolar signature are frequently observed when the Cluster spacecraft fleet passes through both southern and northern high‐latitude energetic electron boundaries at the nightside magnetosphere. The dominant variation of the bipolar signature is in the azimuthal direction of the local mean field‐aligned coordinate, indicating a field‐aligned current. From 2001 to 2008, we have examined 110 events with the magnetic field and energetic electron measurements. The main results can be summarized as follows: (1) The density and thickness of the field‐aligned current, calculated under the assumption of the one‐dimensional sheet, are in order of tens of nA/m 2 and hundreds of kilometers, respectively. (2) Currents flowing into and away from the ionosphere tend to be observed in the postmidnight and premidnight sector, respectively, which have the same polarity as the region 1 current system. (3) These currents mainly distribute in the 60°–75° magnetic latitude region after mapping to the ionosphere. We also find that the current density and corresponding magnetic field variation are positively correlated with the K p index and solar wind pressure, but almost independent of the A E index. Key Points: Field‐aligned current at the high‐latitude energetic electron boundary in the nightside These currents have the same polarity as region 1 current system The current density is positively correlated with K p index and solar wind pressure